Meningkatkan Kemampuan Mengajar Reflektif Guru Bahasa Inggris Berpengalaman dan Baru melalui Observasi/Konferensi Sejawat dan Jurnal Mengajar - Furaidah Furaidah; Utami Widiati (Ilmu Pendidikan: Jurnal Kajian Teori dan Praktik Kependidikan, 2003)
This collaborative action research aimed at increasing teachers' reflective teaching through the use of mutual observation and conference among critical friends, and the writing of teaching journal. It consisted of two cycles and involved two lecturers, two senior teachers, and one junior teacher. In cycle one, mutual observation followed with conference among critical friends resulted in the teachers' more reflective attitude about their teaching performance and better relationship between senior and junior teachers. Though considered to be beneficial, mutual observation needed deeply rooted trust among colleauges that needed long time to grow and neatly arranged teaching schedule. Therefore, in the second cycle, the writing of teaching journal, which then was discussed among critical friends, was taken as alternative.